The effectiveness of a program based on active learning in developing creative thinking skills among students of the Islamic Studies Curriculum Department at the College of Education, Arhab - Al-Harazi, Samia Ali Ahmed; Ghalib, Ahmed Hassan; Al-Afif, Hamid Farhan (Journal of Educational and Psychological Sciences, 2024)
The aim of the study was to determine the effectiveness of a practical education program based on active learning in developing creative thinking skills among students of the Islamic Studies Curriculum Department at Arhab College of Education. The researcher used both the descriptive and quasi-experimental methods with two groups. The program was applied to a total of 40 students, all of whom were in the fourth level of the Islamic Studies Curriculum Department at Arhab College of Education and Applied Sciences in the first semester of the 2022/2023 academic year. The experimental group consisted of 20 male and female students, while the control group also included 20 students. The results revealed statistically significant differences in the post-test scores for creative thinking skills in total. The average score for the control group was 161.90, while the average for the experimental group was 208.95, with a t-value of 9.53 and a significance level of 0.00. The effect size, represented by eta squared, was 0.73, indicating an excellent effect size. In terms of creative thinking skills (fluency, flexibility, originality, problem-solving, and elaboration), the t-values were 3.963, 6.077, 3.303, 4.113, and 7.405, respectively, all significant at α ≤ 0.05. The effect sizes for the creative thinking skills were 0.65, 0.69, 0.63, 0.53, and 0.55, respectively, and the value of Cohen's d was 2.13, indicating a large effect size. This suggests that the independent variable (the active learning-based program) had a 73% effect on the dependent variable (thinking skills), reflecting a large impact. The study recommended integrating active learning principles and creative thinking skills into teacher preparation programs and training teacher students to acquire competencies that enable them to develop creative thinking skills among students in general education. The researcher also suggested conducting additional programs to enhance thinking skills in various disciplines within colleges of education.
Keywords: Active learning; Creative thinking